Corporate Social Responsibility (CSR) by small and medium enterprises (SMEs): a systematic review - Grace Bikefe; Umaru Zubairu; Simeon Araga; Faiza Maitala; Ekanem Ediuku; Daniel Anyebe (Small Business International Review)
This study aims to systematically review the key characteristics and issues in Corporate Social Responsibility among Small and Medium Enterprises (CSRS) research. The Systematic Assessment Quantitative Technique (SQAT) developed by Australian researchers, Catherine Pickering and Jason Antony Byrne, was used to identify and analyse 62 peer-reviewed CSRS articles from six high quality academic databases. Most of the studies took place in Europe and Asia while South America has been largely ignored. A significant number of CSRS research were empirical in nature, meaning that there is a need for more conceptual studies to aid the understanding of new CSRS norms and underlying factors. Additionally, CSRS articles focused mainly on identifying the various ways SMEs are implementing CSR. Finally, most CSRS articles adopted a single research method, with survey being the most dominant method. There is a need for future studies to combine a variety of methods so as to gain additional insight into CSRS related issues